(untitled) (TAMADDUN NURI JURNALI, 2024)
This article explains that for more than two thousand years the problem of "free will" and "free will" has been recognized as one of the discussed topics of philosophy and is the basis for interpreting this topic as an ancient problem. Attention is drawn to the fact that this issue is the subject of study not only of philosophical sciences, but also of psychological sciences. Giving a strict and specific definition of the concepts of "free will" and "freedom of choice" is a difficult task. Philosophers have analyzed the issue of free will and freedom of choice from the point of view of their views. In the philosophical literature devoted to this concept, there is no single definition. In fact, in the context of the discussion, it is argued that these are independent concepts, completely different from each other.